Analysis of the Relationship between Density and Mechanical Strength of Lightened Gypsums: Proposal for a Coefficient of Lightening - Jaime Santa Cruz Astorqui; Mercedes del Río Merino; Paola Villoria Sáez; César Porras-Amores (Advances in Materials Science and Engineering)
This article develops a relationship between the reduction of density in lightened gypsum and the addition of expanded and/or extruded polystyrene waste from the construction sector and their mechanical behavior. The equations determined in this study allow us to know the flexural and compressive strengths of a lightened gypsum/plaster compound once its density is known. The results show that there is an exponential relationship between the density of the compound and its strength. The methodology followed included a compilation of the results obtained in previous research works on lightweight gypsums, analyzing the relationship between density and mechanical strength and comparing them with the equations developed in this research. The results obtained by previous researchers have a good adjustment with the proposed models, and only perlite compounds present greater deviations in the compressive strength analysis. Also, a dimensionless lightening coefficient is defined which can help to determine the best application for a lightweight gypsum compound, comparing it with an ideal lightweight gypsum.